2015
DOI: 10.1021/jacs.5b06637
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Route to Activation of Open Metal Sites in the Copper-Based Metal–Organic Framework Materials HKUST-1 and Cu-MOF-2

Abstract: Open coordination sites (OCSs) in metal-organic frameworks (MOFs) often function as key factors in the potential applications of MOFs, such as gas separation, gas sorption, and catalysis. For these applications, the activation process to remove the solvent molecules coordinated at the OCSs is an essential step that must be performed prior to use of the MOFs. To date, the thermal method performed by applying heat and vacuum has been the only method for such activation. In this report, we demonstrate that methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
197
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(232 citation statements)
references
References 60 publications
(142 reference statements)
19
197
1
4
Order By: Relevance
“…All samples showed good crystallinity. Both XRD patterns are in good agreement with the single-crystal data of Cu 3 (BTC) 2 reported by Kim et al [18], confirming the phase structure of Cu 3 (BTC) 2 . It was also observed that the intensity of the acid-MOF sample decreased due to the surface modification of the Cu 3 (BTC) 2 crystals.…”
Section: Characterization Of Mof Particlessupporting
confidence: 90%
See 1 more Smart Citation
“…All samples showed good crystallinity. Both XRD patterns are in good agreement with the single-crystal data of Cu 3 (BTC) 2 reported by Kim et al [18], confirming the phase structure of Cu 3 (BTC) 2 . It was also observed that the intensity of the acid-MOF sample decreased due to the surface modification of the Cu 3 (BTC) 2 crystals.…”
Section: Characterization Of Mof Particlessupporting
confidence: 90%
“…The main peaks observed in the survey scan are C1s, O1s, and Cu 2p 3/2 peaks centered at 284.5, 531.1, and 934.14 eV, respectively [18][19][20][21]. After acidification of the MOF sample, the Cu 2p 3/2 signature showed different characteristics.…”
Section: Characterization Of Mof Particlesmentioning
confidence: 99%
“…They are difficult to synthesize, however, and are unstable in the aqueous phase. For example, HKUST‐1 (a microporous MOF material with copper as the central ion) that is synthesized by BTC (1,3,5‐benzenetricarboxylic acid) and copper nitrate, will partially collapse if immersed in water for 24 h …”
Section: Introductionmentioning
confidence: 99%
“…Various activation methods have been developed, including thermal activation [37][38][39], solvent exchange [40][41][42], freeze-drying [43,44], supercritical CO 2 exchange [45], and chemical treatment [46,47]. Among these, thermal activation is most commonly used for its simplicity and efficiency.…”
Section: Introductionmentioning
confidence: 99%